LA HISTORIA CULTURAL EN PANAMÁ: UN CAMPO INCIPIENTE. - Miranda , Miriam (2006)
The article approaches the development of the Cultural History in Panama from diverse questioning, such as which has been the path of the historical studies in Panama of a general way?, which are the trends historiographic of major acceptance and spreading in the country?, what is A Cultural History in Panama?, what fields of research are considered to be a part of the cultural Panamanian History? And which are the theoretical and methodological premises that the researchers of the culture use in Panama?. Taking as an axis the reflections of Peter Burke and Roger Chartier with regard to the path followed by the cultural History in the academic international world.